Reversible Inactivation of Rat Premotor Cortex Impairs Temporal Preparation, but not Inhibitory Control, During Simple Reaction-Time Performance - Smith, Nathaniel J.; Horst, Nicole K.; Liu, Benjamine; Caetano, Marcelo S.; Laubach, Mark (Frontiers in Integrative Neuroscience, 2010)
Previous studies by our lab and others have established a role for medial areas of the prefrontal cortex (mPFC) in the top-down control of action during simple reaction-time (RT) tasks. However, the neural circuits that allow mPFC to influence activity in the motor system have remained unclear. In the present study, we used a combination of tract-tracing and reversible inactivation methods to examine the role of a motor-related area in the rat frontal cortex, called the rostral forelimb area (RFA), in the top-down control of action. Neural tracing studies involved used electrical microstimulation to identify RFA and injections of biotinylated dextran amines to map out connections of RFA with other parts of the frontal cortex. Connections were found between RFA and mPFC, the agranular insular cortex, and the primary motor cortex. Reversible inactivations using muscimol infusions into RFA increased response times and eliminated delay-dependent speeding, but did not increase premature responding. These results are markedly different from what is obtained when muscimol is infused into mPFC, which leads to excessive premature responding and a reduction of RTs to stimuli at short delays (Narayanan et al., 2006). We also tested animals during the RT task after inactivating the agranular insular cortex, which contains neurons that projects to and receives from RFA and mPFC, and found no effects on RT performance. Together, these studies suggest that RFA is a premotor region in the rat frontal cortex that competes with mPFC to control action selection. We suggest that RFA controls the threshold that is used to initiate responding and generates prepotent excitation over responding that is crucial for temporal preparation.